Three dimensional analysis of point-bearing pile groups - Ayalp, Mehmet. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
Piles in the foundation of structures like bridge piers, quays, retaining walls and the like are usually installed in groups resulting in a group reaction.This brings about the problem of determining the distribution of this reaction among individual piles in the group. Especially, if a group of piles consists of both vertical and battered piles, if there are both horizontal and vertical loads or if the loads on the group are eccentric with respect to the pile group, the question of what load is carried by each pile in the group naturally arises. This study attempts to develop a computer program providing the three dimensional analysis of such systems. Here it is assumed that external loads from the superstructure are transferred to the piles through an infinitely rigid pile cap, and piles reach the bearing strata. Each pile is idealized as a beam having a uniformly distributed linearly elastic spring reaction in the lateral direction. Thus; shears, axial forces and moments acting on the piles within the group are determined. The displacements and rotations of each single pile are also calculated. The results of the analysis are checked against the solutions of some particular examples given in the literature.
Keywords: Piling (Civil engineering); Concrete piling.